Establishing an Online Writing Centre: Understanding Writing Consultants’ Perceptions and Experiences of Synchronous Virtual One-to-One Tutoring - Yu Hang Kwan (Studies in Self-Access Learning Journal)
Considering the insufficient studies of the maintenance of self-access learning support and the implementation of remote writing tutoring during the coronavirus pandemic, this article fills this gap by describing two undergraduate and two postgraduate writing centre consultants’ perceptions and experiences of synchronous virtual one-to-one tutoring via web conferencing. The four consultants’ views were elicited through individual semi-structured interviews, which were then transcribed verbatim and analysed using thematic content analysis. The interview findings revealed that the four consultants all considered synchronous virtual tutoring a viable alternative to face-to-face tutoring. While the undergraduate consultants highlighted the convenience and efficiency of web conferencing, the postgraduate consultants encountered personal challenges and issues with web conferencing. Three recommendations for consultant training and tutoring are proposed: using a collaborative writing tool, sensitising consultants to skills for facilitating online interactions, and reminding students of the ‘netiquette’ for web-based tutoring. In light of the continuing technological advancement and the increasing demand for distance education, the findings and recommendations will offer a point of reference to writing centre administrators and consultants for the implementation of synchronous virtual tutoring and the inclusion of web conferencing skills in consultant training.